PENGARUH KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN PEMBAYARAN PAJAK : ANALISIS BIBLIOMETRIK - Agustina, Hanugalih Elda (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
This research aims to map research topics and develop further research directions related to the influence of taxpayer awareness on tax payment compliance. This research also allows the author to obtain potential new keywords to be used as future research topics. This research is a literature study with a bibliometric analysis method to analyze 376 articles related to taxpayer awareness of tax payment compliance. Bibliometric analysis was conducted using the VOSviewer analysis tool. Articles were obtained from the Google Scholar database accessed through Publish or Perish in the 2019-2023 range. The results obtained by this study are that topics related to taxpayer awareness of tax payment compliance are interesting topics to research. There are several specific words that have the potential to be further researched related to the topic of taxpayer awareness of tax payment compliance, namely, services, sanctions, satisfaction, and motor vehicle tax. This research is expected to contribute ideas and thoughts for further research to be more directed.Keywords: Compliance; Tax Payment; Taxation